KAJIAN PENEGAKAN HUKUM PASCA PEMILIHAN KEPALA DAERAH (Mempertanyakan Komitmen Pemenang Pilkada dalam Penegakan Hukum dan Pemberantasan Korupsi di Daerah) - Zulkarnain, Zulkarnain (Jurnal Konstitusi, 2010)
Law enforcement in the process of local head elections often becomes a moment platform for the candidates as a strategy to be winners. But, after the election, the law enforcement is hard to do. The winner chooses to be  passive to the law violation made by his ‘political friend” and repressive to his ‘opponents’ and the low status.  There are many law violations that cannot be completely solved since the violators are his or her team during the election. This often happens when the violators are his or her donators. Therefore, law enforcement is coopted by political requite and